Systemic inflammatory response in colorectal cancer is associated with tumour mismatch repair and impaired survival - Hjortborg, Mats; Edin, Sofia; Böckelman, Camilla; Kaprio, Tuomas; Li, Xingru; Gkekas, Ioannis; Hagström, Jaana; Strigard, Karin; Haglund, Caj; Gunnarsson, Ulf; Palmqvist, Richard (NATURE PORTFOLIO, 2025)
The systemic inflammatory response (SIR), defined as elevated levels of circulating C-reactive protein (CRP), is an important predictor of impaired survival in colorectal cancer. The aim of this study was to explore the prognostic role of SIR and its association with tumour mismatch repair status and the immune response. Immune activity profiles of mononuclear cells isolated from CRC tissues and blood in the U-CAN exploration cohort (n = 69), were analysed by flow cytometry. In the U-CAN validation cohort (n = 257), T-helper cells (T-bet(+)), cytotoxic T cells (CD8(+)), regulatory T cells (FoxP3(+)), B cells (CD20(+)), and macrophages (CD68(+)) were analysed by multispectral imaging. Microsatellite instability was determined using five mononucleotide-repeat microsatellite markers. Patients with high CRP levels (> 10 mg/l) were significantly more often diagnosed with high-grade tumours and tumours exhibiting microsatellite instability. However, some patients with high CRP levels were found to have microsatellite-stable tumours. Furthermore, high CRP levels were associated with specific tumour immune traits including an augmented macrophage response and were significantly linked to poorer cancer-specific survival, particularly in patients with microsatellite-stable tumours. In conclusion, our findings suggest an interplay between SIR and mismatch repair status in CRC prognosis which needs to be further explored.